Experimental evidence that polystyrene nanoplastics cross the intestinal barrier of European seabass. (August 2022) - Vagner, M.; Boudry, G.; Courcot, L.; Vincent, D.; Dehaut, A.; Duflos, G.; Huvet, A.; Tallec, K.; Zambonino-Infante, J.-L.
Graphical abstract: Highlights: Plastic particles crossing the intestinal barrier is debated. PS-NP particles were tested in ex-vivo time series experiments using Ussing chambers. Two PS-NP concentrations were tested on two locations of adult Seabass guts. PS-NP directly crossed the intestinal barrier of adult Seabass within few minutes. PS-NP translocation was confirmed by 3 complementary techniques. Abstract: Plastic pollution in marine ecosystems constitutes an important threat to marine life. For vertebrates, macro/microplastics can obstruct and/or transit into the airways and digestive tract whereas nanoplastics (NPs; < 1000 nm) have been observed in non-digestive tissues such as the liver and brain. Whether NPs cross the intestinal epithelium to gain access to the blood and internal organs remains controversial, however. Here, we show directly NP translocation across the intestinal barrier of a fish, the European seabass, Dicentrarchus labrax, ex vivo . The luminal side of median and distal segments of intestine were exposed to fluorescent polystyrene NPs (PS-NPs) of 50 nm diameter. PS-NPs that translocated to the serosal side were then detected quantitatively by fluorimetry, and qualitatively by scanning electron microscopy (SEM) and pyrolysis coupled to gas chromatography and high-resolution mass spectrometry (Py-GC-HRMS). Fluorescence intensity on the serosal side increased 15–90 min after PS-NP addition into the luminal side, suggesting that PS-NPs crossed the intestinal barrier; this was confirmed by both SEM and Py-GC-HRMS. This study thus evidenced conclusively that NPs beads translocate across the intestinal epithelium in this marine vertebrate.